Glucagon-like peptide-1 receptor agonist therapeutics for total diabetes management: assessment of composite end-points. (July 2015) - Yabe, Daisuke; Kuwata, Hitoshi; Usui, Ryota; Kurose, Takeshi; Seino, Yutaka
Abstract Assessment of the benefits of anti-diabetic drugs for type 2 diabetes requires analysis of composite end-points, taking HbA1c, bodyweight, hypoglycemia and other metabolic parameters into consideration; continuous, optimal glycemic control as well as bodyweight, blood pressure and lipid levels are critical to prevent micro- and macro-vascular complications. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are now established as an important total treatment strategy for type 2 diabetes, exerting glucose-lowering effects with little hypoglycemia risk and also ameliorating bodyweight, blood pressure and lipid levels, which are therapeutic targets for prevention of complications of the disease. The available data strongly suggest only beneficial effects of GLP-1RAs; however, long-term evaluation of the relevant composite end-points including health-related quality of life and cost-effectiveness remain to be investigated in adequately powered, prospective, controlled clinical trials. In the meantime, healthcare professionals need to be scrupulously attentive for potential, rare adverse events in patients using GLP-1RAs.